A modified fly ash and its preparation method and application
By using fly ash, carbide slag and other raw materials, combined with wet ball milling and other processes, modified fly ash is prepared, which solves the problem of limited application of fly ash in building materials and achieves high efficiency of modified fly ash. Mechanical properties and fluidity reduce production costs and are suitable for mass production.
Patent Information
- Application Number
- CN202410834931.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-26
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-06-26
AI Technical Summary
The application of fly ash in building materials is limited by its different particle sizes, low activity index and slow hydration speed, which affects the early strength of concrete. The existing modification methods are costly and complex in technology, so they are not suitable for large-scale production.
Using raw materials such as fly ash, carbide slag, triisopropanolamine, sodium sulfate and modified graphene oxide, modified fly ash is prepared through wet ball milling and other processes to improve its mechanical properties and fluidity.
The prepared modified fly ash has excellent mechanical properties, high early strength and late strength, good fluidity, meets the requirements of building materials, reduces production costs, and is suitable for large-scale production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and specifically relates to modified fly ash and a preparation method and application thereof. Background Art
[0002] With the rapid development of the power industry, the amount of fly ash discharged from coal-fired power plants has increased year by year. If these fly ashes are not treated, they will cause serious environmental problems. On the one hand, they will occupy a lot of land if they are piled up in the open air; on the other hand, if they are not controlled, they will generate dust and pollute the atmosphere; if they are discharged into the water system, they will also cause river siltation, and the harmful chemicals in them will also cause harm to humans and organisms. However, compared with other volcanic ash materials, fly ash has low hydration heat, good corrosion resistance, and large specific surface area. It is particularly suitable for large-volume concrete and industrial and civil buildings. As a mixed material for cement, it can not only reduce the amount of cement clinker and reduce costs, but also realize the effective utilization of resources and turn harm into benefit. However, the fly ash particles are of different sizes, have a low activity index, and a slow hydration rate, which affects the early strength of concrete, which limits its application in building materials.
[0003] In order to solve these problems, researchers began to explore methods to modify fly ash, mainly including physical modification and chemical modification. Physical modification methods such as high-temperature thermal modification and mechanical force activation mainly enhance the performance of fly ash by changing its physical structure or morphology. Although the cost is low, the modification effect is limited. The chemical modification method is to add certain additives to fly ash to control its physical and chemical properties to form modified fly ash. Although the modification effect is good, the process is uncontrollable, the process is complicated, the cost is high, and it is not suitable for large-scale production.
[0004] Therefore, there is an urgent need for a method for modifying fly ash, which can not only improve the modification effect and the performance of cement-based materials, but also be easy to operate and can be mass-produced. Summary of the invention
[0005] The purpose of the present invention is to provide a modified fly ash and its preparation method and application, wherein the modified fly ash has excellent mechanical properties, high fluidity, and meets the requirements of building materials. At the same time, the modified fly ash uses fly ash as raw material, which saves costs and increases economic benefits. In order to achieve the above purpose, the present invention provides the following technical solutions:
[0006] A modified fly ash comprises, by weight, 95-105 parts of fly ash, 5-25 parts of carbide slag, 0.2-3 parts of triisopropanolamine, 1-3 parts of sodium sulfate, 0.05-0.2 parts of modified graphene oxide and 100-200 parts of water.
[0007] Preferably, the density of the fly ash is ≤2.5g / cm3 , specific surface area ≥350m 2 / kg, the mass fraction of CaO is ≤8%; further preferably, the density of the fly ash is 2.2g / cm 3 , specific surface area ≥400m 2 / kg, the mass fraction of CaO ≤6%.
[0008] In some preferred embodiments, the fly ash is purchased from Henan Borun Casting Materials Co., Ltd.
[0009] Preferably, the mass fraction of calcium oxide in the carbide slag is ≥70%, and the particle size is ≤150 μm; further preferably, the mass fraction of calcium oxide in the carbide slag is ≥80%, and the particle size is ≤75 μm.
[0010] In some preferred embodiments, the carbide slag is purchased from Gongyi Qianghong Water Purification Materials Co., Ltd.
[0011] Preferably, the mass ratio of the fly ash to carbide slag is (4-10):1; further preferably, it is 5:1.
[0012] In some preferred schemes, the present application selects specific fly ash and carbide slag, and when the mass ratio of the fly ash to the carbide slag is (4-10):1, the activity index of the modified fly ash can be increased while the early strength of the modified fly ash is increased. This may be because, on the one hand, the alkaline substances such as calcium oxide contained in the carbide slag can react with the active substances in the fly ash such as silicon dioxide and aluminum oxide under wet ball milling conditions to generate substances such as hydrated calcium silicate and hydrated calcium aluminate with high strength and water hardness. On the other hand, the carbide slag provides a strong alkaline environment for the hydration of the fly ash, thereby improving the early strength of the modified fly ash and improving its activity. In addition, the carbide slag is also a solid waste. Using it as one of the raw materials for modified fly ash can reduce costs and increase economic benefits. In practical applications, the present applicant unexpectedly found that excessive carbide slag will cause the hydration product to precipitate from the solution prematurely and cover the fly ash particles, affecting the continued reaction of the fly ash and reducing the strength of the fly ash. Therefore, in practical application, the amount of carbide slag added should be appropriate. However, the addition of carbide slag alone has limited effect on improving the performance of modified fly ash.
[0013] Preferably, the effective ingredient content of the triisopropanolamine is ≥80%, and the boiling point is 150-190°C; further preferably, the effective ingredient content of the triisopropanolamine is ≥85%, and the boiling point is 170-180°C.
[0014] In some preferred embodiments, the triisopropanolamine is industrial grade and purchased from Guan Jiuzhou (Shandong) Energy Technology Co., Ltd.
[0015] Preferably, the mass ratio of the fly ash, carbide slag and triisopropanolamine is (35-80):(5-15):1; more preferably, it is 50:10:1.
[0016] In traditional industrial production, considering the actual cost issue, the modification of fly ash is mostly limited to grinding, which increases the specific surface area of fly ash and thus improves its activity. However, grinding alone has limited effect on the improvement of fly ash activity, and a longer grinding time, at least 1.5 hours, is required to achieve a better grinding effect. The ground fly ash is also prone to agglomeration when used in cement systems due to its small particle size. The applicant creatively discovered that by selecting a specific triisopropanolamine, and the mass ratio of fly ash, carbide slag and triisopropanolamine is (35~80): (5~15): 1, the early strength of the modified fly ash can be further improved while also improving the ball milling efficiency. This may be because during the ball milling process, collisions between carbide slag and fly ash of different particle sizes occur, increasing the number of particles in the system, making the collision and friction between the grinding balls and the materials more frequent and intense, causing the dense glass structure on the surface of the fly ash to be destroyed, facilitating the polar groups in triisopropanolamine to reduce the surface tension between fly ash particles, thereby increasing the specific surface area of fly ash particles while preventing the agglomeration of particles. At the same time, triisopropanol and carbide slag composites react with fly ash to generate a certain amount of calcium sulfonate, thereby improving the strength of the final product. However, considering that excessive triisopropanolamine will affect the cement hydration process, increase the shrinkage of cement, cause concrete to be prone to cracks and deformation, and affect the strength of cement-based materials, the amount of triisopropanolamine added should not be too much, and the amount of calcium sulfonate generated is also limited.
[0017] The CAS number of the sodium sulfate is: 7757-82-6.
[0018] Preferably, the amount of sodium sulfate added is 1% to 2% of the total mass of fly ash and carbide slag.
[0019] The applicant unexpectedly discovered that, on the basis of carbide slag and triisopropanolamine, the addition of 1% to 2% sodium sulfate to the total mass of fly ash and carbide slag can improve the early and late strength of fly ash and further stimulate its activity. This may be because, on the one hand, sodium sulfate reacts with alumina in fly ash under the alkaline conditions created by carbide slag to form calcium sulfate, forming a rod-shaped or fibrous coating on the surface of fly ash particles, which is convenient for Ca 2+It diffuses into the fly ash particles, reacts with the active substances inside, and contains more crystal water, which can reduce the porosity of the system to a certain extent and improve the early strength of the system. On the other hand, under the condition of water-added ball milling, the water-soluble sodium sulfate can also react with carbide slag to generate highly dispersed calcium sulfate, which increases the generation rate of calcium sulfonate. The generated sodium hydroxide can also increase the alkalinity of the system, thus achieving a double excitation effect and greatly improving the early strength and activity of the modified fly ash. However, due to the expansion of calcium sulfonate, excessive generation will lead to cracking of the final product, so the amount of sodium sulfate added needs to be controlled.
[0020] The method for preparing the modified graphene oxide comprises the following steps, measured by weight:
[0021] S1: 1 part of vinyl silane and 0.2-0.4 parts of graphene oxide are mixed in 15-25 parts of ethanol aqueous solution, and after ultrasonic treatment at 30-50W for 20-40min, a solid is obtained by filtration, and the solid is dried to constant weight to obtain substance 1;
[0022] S2: Mix 0.4-0.8 parts of substance 1, 3-8 parts of monomer, and 150-200 parts of water, heat in a water bath at 30-45°C and stir evenly, add a chain transfer agent, continue the reaction for 0.5-1.5 hours, add an initiator, react for 2-4 hours, add a neutralizer to adjust the pH of the solution to 7, filter to obtain a solid, and dry the solid to constant weight to obtain modified graphene oxide.
[0023] Preferably, the vinyl silane is one or more of vinyl trimethoxy silane, vinyl methyl dimethyloxy silane, and vinyl triethoxy silane; more preferably, it is vinyl triethoxy silane.
[0024] Preferably, the graphene oxide includes single-layer graphene oxide and multi-layer graphene oxide.
[0025] Preferably, the weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1:(0.5-2); further preferably, it is 1:1.
[0026] Preferably, the average thickness of the single-layer graphene oxide is 0.5-1.2 nm, and the diameter is 4-7 μm.
[0027] Preferably, the multilayer graphene oxide has an average thickness of 1 to 3 nm, a diameter of 4 to 7 μm, and 2 to 5 layers.
[0028] In some preferred embodiments, the single-layer graphene oxide and the multi-layer graphene oxide are both purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.
[0029] Preferably, the volume concentration of the ethanol aqueous solution is 90% to 98%.
[0030] Preferably, the monomers include polyether macromonomers and unsaturated acids.
[0031] Preferably, the molar ratio of the polyether macromonomer to the unsaturated acid is (2-4):1; more preferably, it is 3:1.
[0032] Preferably, the polyether macromonomer is one or more of isopentenyl polyoxyethylene ether, allyl polyoxyethylene ether, methylallyl polyoxyethylene ether, and isobutylene alcohol polyoxyethylene ether; further preferably, it is methylallyl polyoxyethylene ether.
[0033] Preferably, the hydroxyl value of the methyl allyl polyoxyethylene ether is 15-30 mgKOH / g, and the molecular weight is 1900-2800; further preferably, the hydroxyl value of the methyl allyl polyoxyethylene ether is 21-26 mgKOH / g, and the molecular weight is 2160-2640.
[0034] In some preferred embodiments, the methyl allyl polyoxyethylene ether is purchased from Shijiazhuang Haisen Chemical Co., Ltd.
[0035] Preferably, the unsaturated acid is one or more of acrylic acid, itaconic acid, methacrylic acid, and maleic anhydride; more preferably, it is acrylic acid.
[0036] Preferably, the chain transfer agent is one or more of 2-mercaptoethanesulfonic acid, mercaptopropionic acid, dodecanethiol, and isopropanol; more preferably, it is isopropanol.
[0037] Preferably, the amount of the chain transfer agent added is 1% to 3% of the total mass of the raw materials in step S2; more preferably, it is 2%.
[0038] Preferably, the initiator is one or more of ammonium persulfate, sodium bisulfite, benzoyl peroxide, sodium persulfate, and sodium hypophosphite; further preferably, it is ammonium persulfate and sodium bisulfite.
[0039] Preferably, the weight ratio of ammonium persulfate to sodium bisulfite is 1:(0.5-2); further preferably, it is 1:1.
[0040] Preferably, the amount of the initiator added is 0.5% to 2% of the total mass of the raw materials in step S2; more preferably, it is 1.2%.
[0041] Preferably, the neutralizing agent is sodium hydroxide.
[0042] In some preferred schemes, fly ash is modified by selecting specific single-layer graphene oxide and multi-layer graphene oxide, and the weight ratio of the single-layer graphene oxide and the multi-layer graphene oxide is 1: (0.5~2), which can improve the early strength performance of the modified fly ash while ensuring the strength stability of the matrix. This may be because the single-layer and multi-layer graphene oxide structures selected in this application have similar diameters and little difference in thickness, so there is a certain compounding effect between the two. On the one hand, the complementarity in the number of layers is achieved, which not only retains the high activity of the single-layer graphene oxide, but also improves the stability of the overall structure. It can effectively fill the internal gaps of cement-based materials, and provide additional nucleation sites for the growth of hydration products, thereby improving the strength of cement-based materials in many ways. On the other hand, single-layer and multi-layer graphene oxides of similar sizes can be intertwined and stacked to form a stable three-dimensional network structure, which can effectively prevent the expansion of cracks, thereby improving the strength of cement-based materials. However, the particle size of graphene oxide is nanometer-scale and prone to agglomeration. At the same time, its high chemical reactivity will accelerate the hydration process, promote the solidification of the matrix, affect the fluidity of the matrix, and is not conducive to actual production.
[0043] The applicant unexpectedly discovered that the modification of graphene oxide using the method and raw materials in this application can improve the early strength of the modified fly ash while stabilizing the fluidity of the matrix and ensuring smooth production. This may be because the present application first grafts carbon-carbon double bonds on graphene oxide through pretreatment, which is convenient for copolymerization with monomers to generate modified graphene oxide containing a polycarboxylic acid water-reducing agent structure. When applied to building materials, it can enhance the strength of the matrix while enhancing the workability during the preparation process, improve the slow setting phenomenon when only graphene oxide is added, and the modified graphene oxide has better compatibility with the raw materials than directly adding polycarboxylic acid water-reducing agents, and has a better modification effect on fly ash. In addition, the surface of the modified graphene oxide will adsorb a large amount of fly ash particles with a lubricating effect, thereby reducing the friction between graphene oxide and cement-based materials in actual applications, improving the fluidity of the slurry, and ensuring smooth production.
[0044] Although the stability of graphene oxide can be improved by appropriate methods, excess graphene still has the risk of agglomeration. In addition, graphene oxide is expensive, and using too much will increase costs, which is not conducive to industrial production.
[0045] The second aspect of the present invention provides a method for preparing the modified fly ash, comprising the following steps:
[0046] The raw materials are mixed according to weight and wet-milled to obtain modified fly ash.
[0047] Preferably, the specific conditions of the wet ball milling are: a rotation speed of 500-700 r / min, and a ball milling time of 20-40 min; further preferably, the specific conditions of the wet ball milling in step S2 are: a rotation speed of 600 r / min, and a ball milling time of 30 min.
[0048] Preferably, during the wet ball milling process, the mass ratio of the ball milling medium to the fly ash is (2-4):1; further preferably, it is 3:1.
[0049] Preferably, the ball milling medium is yttrium stabilized zirconia beads.
[0050] Preferably, the yttrium content in the yttrium-stabilized zirconia beads is 5 wt % and the particle size is 15 mm.
[0051] In some preferred embodiments, the yttrium-stabilized zirconia beads are purchased from Shandong Qitai Industrial Ceramics Co., Ltd.
[0052] The third aspect of the present invention provides the application of the modified fly ash in cement-based building materials.
[0053] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0054] The present invention provides a modified fly ash, which uses solid waste modified fly ash and carbide slag as main raw materials, has low production cost, not only reduces cost, but also brings certain economic benefits to enterprises through the reuse of solid waste. Compared with the prior art, the modified fly ash prepared by the present invention has excellent mechanical properties, high early strength and late strength, good fluidity, and meets the requirements of cement-based building materials. At the same time, the process operation is simple, easy to implement, and convenient for promotion.
[0055] The present invention selects specific fly ash and carbide slag, and when the mass ratio of the fly ash to the carbide slag is (4-10):1, the activity index of the modified fly ash can be improved while the early strength of the modified fly ash is improved.
[0056] The present invention selects a specific triisopropanolamine, and the mass ratio of the fly ash, carbide slag and triisopropanolamine is (35-80): (5-15): 1, which can further improve the early strength of the modified fly ash and improve the ball milling efficiency. The present invention adds 1% to 2% of the total mass of fly ash and carbide slag. The early strength and late strength of the fly ash are improved and its activity can be further stimulated.
[0057] The present invention selects specific single-layer graphene oxide and multi-layer graphene oxide to modify fly ash, and the weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1: (0.5-2), which can improve the early strength performance of the modified fly ash while ensuring the strength stability of the matrix.
[0058] The method and raw materials in the present application are used to modify graphene oxide, which can improve the early strength of the modified fly ash while stabilizing the fluidity of the matrix and ensuring smooth production.
[0059] This application uses physical wet ball milling in combination with specific chemical substances to modify fly ash. The raw materials and treatment methods have a compatible effect. Not only can the modification effect be guaranteed while reducing the ball milling time, reducing energy consumption, and alleviating the production cost of the enterprise, but the prepared modified fly ash has high early and late strengths, good fluidity, and a friendly activity index. It can be used in cement-based materials to replace part of the cement, bringing certain economic benefits to the enterprise. Fly ash and carbide slag are both solid wastes. Using them as raw materials is not only low-cost, but also highly economical, and has certain environmental protection significance. DETAILED DESCRIPTION
[0060] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0061] The raw materials used in the present invention are all commercially available, specifically:
[0062] Fly ash, density is 2.2g / cm 3 , specific surface area ≥400m 2 / kg, the mass fraction of CaO ≤6%, purchased from Henan Borun Casting Materials Co., Ltd.
[0063] Carbide slag, with a mass fraction of calcium oxide ≥ 80% and a particle size ≤ 75 μm, was purchased from Gongyi Qianghong Water Purification Materials Co., Ltd.
[0064] Triisopropanolamine, with an active ingredient content of ≥85% and a boiling point of 170-180°C, was purchased from Guan Jiuzhou (Shandong) Energy Technology Co., Ltd.
[0065] The average thickness of single-layer graphene oxide is 0.5~1.2nm, and the diameter is 4~7μm; the average thickness of multi-layer graphene oxide is 1~3nm, the diameter is 4~7μm, and the number of layers is 2~5; both were purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.
[0066] Methyl allyl polyoxyethylene ether, with a hydroxyl value of 21-26 mgKOH / g and a molecular weight of 2160-2640, was purchased from Shijiazhuang Haisen Chemical Co., Ltd.
[0067] The remaining raw materials were of analytical grade and purchased commercially.
[0068] (1) Example 1
[0069] The present embodiment provides a modified fly ash, and the raw materials for its preparation are, by weight: 100 parts of fly ash, 20 parts of carbide slag, 2 parts of triisopropanolamine, 2 parts of sodium sulfate, 0.1 parts of modified graphene oxide, and 150 parts of water.
[0070] The preparation method of the modified graphene oxide comprises the following steps, calculated by weight:
[0071] S1: 1 part of vinyl silane and 0.3 parts of graphene oxide were mixed in 20 parts of 95% ethanol aqueous solution, and after ultrasonic treatment at 40W for 30 minutes, a solid was obtained by filtration, and the solid was dried to constant weight to obtain substance 1;
[0072] S2: 0.5 parts of substance 1, 5 parts of monomer and 180 parts of water were mixed, heated in a water bath at 40°C and stirred evenly, a chain transfer agent was added, the reaction was continued for 1 hour, an initiator was added, the reaction was continued for 3 hours, a neutralizer was added to adjust the pH of the solution to 7, a solid was obtained by filtering, and the solid was dried to constant weight to obtain modified graphene oxide.
[0073] The vinyl silane is vinyl triethoxy silane.
[0074] The graphene oxide is single-layer graphene oxide and multi-layer graphene oxide.
[0075] The weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1:1.
[0076] The monomers are polyether macromonomers and unsaturated acids.
[0077] The molar ratio of the polyether macromonomer to the unsaturated acid is 3:1.
[0078] The polyether macromonomer is methyl allyl polyoxyethylene ether.
[0079] The unsaturated acid is acrylic acid.
[0080] The chain transfer agent is isopropyl alcohol.
[0081] The amount of the chain transfer agent added is 2% of the total mass of the raw materials in step S2.
[0082] The initiators are ammonium persulfate and sodium bisulfite.
[0083] The weight ratio of the ammonium persulfate to the sodium bisulfite is 1:1.
[0084] The amount of the initiator added is 1.2% of the total mass of the raw materials in step S2.
[0085] The neutralizing agent is sodium hydroxide.
[0086] The preparation method of the modified fly ash comprises the following steps:
[0087] The modified fly ash is obtained by mixing the raw materials for preparing the modified fly ash according to a weight ratio and wet-ball milling the mixture.
[0088] The specific conditions of the wet ball milling are: the mass ratio of ball milling medium to fly ash is 3:1, the rotation speed is 600r / min, and the ball milling time is 30min.
[0089] (2) Example 2
[0090] The difference between this embodiment and embodiment 1 is that the modified fly ash is prepared from the following raw materials, by weight: 100 parts of fly ash, 25 parts of carbide slag, 2 parts of triisopropanolamine, 2.5 parts of sodium sulfate, 0.15 parts of modified graphene oxide, and 180 parts of water.
[0091] (3) Embodiment 3
[0092] The difference between this embodiment and embodiment 1 is that the modified fly ash is prepared from the following raw materials, by weight: 100 parts of fly ash, 20 parts of carbide slag, 2 parts of triisopropanolamine, 2 parts of sodium sulfate, 0.2 parts of modified graphene oxide, and 150 parts of water.
[0093] The weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1:2.
[0094] Comparative Example 1
[0095] The difference between this comparative example and Example 1 is that the modified fly ash is prepared from the following raw materials, by weight: 100 parts of fly ash, 30 parts of carbide slag, 2 parts of triisopropanolamine, 2 parts of sodium sulfate, 0.1 parts of modified graphene oxide, and 150 parts of water.
[0096] Comparative Example 2
[0097] The difference between this comparative example and Example 1 is that the modified fly ash is prepared from the following raw materials, by weight: 100 parts of fly ash, 20 parts of carbide slag, 5 parts of triisopropanolamine, 2 parts of sodium sulfate, 0.1 parts of modified graphene oxide, and 150 parts of water.
[0098] Comparative Example 3
[0099] The difference between this comparative example and Example 1 is that the modified fly ash is prepared from the following raw materials, by weight: 100 parts of fly ash, 20 parts of carbide slag, 2 parts of triisopropanolamine, 4 parts of sodium sulfate, 0.1 parts of modified graphene oxide, and 150 parts of water.
[0100] Comparative Example 4
[0101] The difference between this comparative example and Example 1 is that the modified fly ash is prepared from the following raw materials, by weight: 100 parts of fly ash, 20 parts of carbide slag, 2 parts of triisopropanolamine, 2 parts of sodium sulfate, 0.1 parts of graphene oxide, and 150 parts of water.
[0102] The graphene oxide is single-layer graphene oxide and multi-layer graphene oxide.
[0103] The weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1:1.
[0104] Comparative Example 5
[0105] The difference between this comparative example and Example 1 is that the modified fly ash is prepared from the following raw materials, by weight: 100 parts of fly ash, 20 parts of carbide slag, 2 parts of triisopropanolamine, 2 parts of sodium sulfate, 0.1 parts of graphene oxide, 1 part of polycarboxylic acid water reducer, and 150 parts of water.
[0106] The graphene oxide is single-layer graphene oxide and multi-layer graphene oxide.
[0107] The weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1:1.
[0108] The polycarboxylate water reducer has an effective ingredient of ≥90%, a water reduction rate of ≥25%, and a water content of ≤3%, and is purchased from Shandong Zhongwei High-tech Materials Co., Ltd.
[0109] Comparative Example 6
[0110] The difference between this comparative example and Example 1 is that the modified fly ash is prepared from the following raw materials, by weight: 100 parts of fly ash, 20 parts of carbide slag, 2 parts of triisopropanolamine, 2 parts of sodium sulfate, 0.5 parts of modified graphene oxide, and 150 parts of water.
[0111] Comparative Example 7
[0112] The difference between this comparative example and Example 1 is that the multilayer graphene oxide has an average thickness of 3.4-8 nm, a diameter of 10-50 μm, and 5-10 layers.
[0113] The multilayer graphene oxide was purchased from Shenzhen Liyou New Energy Technology Co., Ltd.
[0114] Performance Testing
[0115] Referring to GB / T 1596-2017 "Fly ash used in cement and concrete", the modified fly ash prepared in each embodiment and comparative example was prepared into a mortar test block, and its 7d compressive strength, 28d compressive strength, strength activity index and fluidity were tested and compared with the untreated fly ash. The results are shown in Table 1.
[0116]
[0117] According to statistics, the modified fly ash prepared in Examples 1 to 3 of the present invention has a 7d compressive strength of >30MPa, a 28d compressive strength of >50MPa, a strength activity index of >95%, and a fluidity of >260mm. In Comparative Example 1, the amount of carbide slag is excessive, in Comparative Example 2, the amount of triisopropanolamine is excessive, in Comparative Example 3, the amount of sodium sulfate is excessive, in Comparative Example 4, the graphene oxide is not modified, in Comparative Example 5, a polycarboxylic acid water reducer is used to improve the fluidity of the system, in Comparative Example 6, the amount of modified graphene oxide is excessive, and in Comparative Example 7, the physical properties of multilayer graphene oxide are not within the scope of the present application. The mortar test blocks prepared from the modified fly ash do not fully meet the requirements. Therefore, the modified fly ash prepared using the raw materials and methods described in the present application has good early strength and late strength, high activation index, good fluidity, can be applied to the field of building materials, and has low cost and good economic benefits.
[0118] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A modified fly ash, characterized in that: The raw materials for its preparation include, by weight: 95-105 parts of fly ash, 5-25 parts of carbide slag, 0.2-3 parts of triisopropanolamine, 1-3 parts of sodium sulfate, 0.05-0.2 parts of modified graphene oxide, and 100-200 parts of water; the density of the fly ash is ≤2.5g / cm 3 , specific surface area ≥350m 2 / kg, the mass fraction of CaO ≤8%; the mass fraction of calcium oxide in the carbide slag ≥70%, the particle size ≤150μm; the effective ingredient content in the triisopropanolamine ≥80%, the boiling point is 150~190℃; the mass ratio of the fly ash, carbide slag and triisopropanolamine is (35~80): (5~15): 1; the addition amount of sodium sulfate is 1%~2% of the total mass of fly ash and carbide slag; The method for preparing the modified graphene oxide comprises the following steps, measured by weight: S1: 1 part of vinyl silane and 0.2-0.4 parts of graphene oxide are mixed in 15-25 parts of ethanol aqueous solution, and after ultrasonic treatment at 30-50W for 20-40min, a solid is obtained by filtration, and the solid is dried to constant weight to obtain substance 1; S2: 0.4-0.8 parts of substance 1, 3-8 parts of monomer, and 150-200 parts of water are mixed, heated in a water bath at 30-45°C and stirred evenly, a chain transfer agent is added, the reaction is continued for 0.5-1.5 hours, an initiator is added, the reaction is continued for 2-4 hours, a neutralizer is added to adjust the solution pH to 7, a solid is obtained by filtration, and the solid is dried to a constant weight to obtain modified graphene oxide; The graphene oxide includes a single-layer graphene oxide and a multi-layer graphene oxide; the weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1:(0.5-2); the average thickness of the single-layer graphene oxide is 0.5-1.2 nm, and the diameter is 4-7 μm; the average thickness of the multi-layer graphene oxide is 1-3 nm, the diameter is 4-7 μm, and the number of layers is 2-5; The monomers include polyether macromonomers and unsaturated acids, wherein the molar ratio of the polyether macromonomers to the unsaturated acids is 3:1; the polyether macromonomers are methyl allyl polyoxyethylene ethers, the hydroxyl value of the methyl allyl polyoxyethylene ethers is 21-26 mgKOH / g, the molecular weight is 2160-2640, and the unsaturated acid is acrylic acid.
2. The modified fly ash according to claim 1, characterized in that: The vinyl silane is one or more of vinyl trimethoxy silane and vinyl triethoxy silane.
3. A method for preparing the modified fly ash according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: mixing raw materials according to weight parts and wet ball grinding to obtain modified fly ash.
4. The method for preparing modified fly ash according to claim 3, characterized in that: The specific conditions of the wet ball milling are: a rotation speed of 500-700 r / min and a ball milling time of 20-40 min.
5. The method for preparing modified fly ash according to claim 3, characterized in that: During the wet ball milling process, the mass ratio of the ball milling medium to the fly ash is (2-4):
1.
6. An application of the modified fly ash according to any one of claims 1-2, characterized in that: Used in cement-based building materials.
Citation Information
Patent Citations
Desulfurization ash-coal ash complex mineral admixture and preparation method thereof
CN106220013A
Silane modified graphene oxide modified polycarboxylic acid reducer and preparation method thereof
CN109942221A